2021
DOI: 10.3390/plants10050921
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipases C and D and Their Role in Biotic and Abiotic Stresses

Abstract: Plants, as sessile organisms, have adapted a fine sensing system to monitor environmental changes, therefore allowing the regulation of their responses. As the interaction between plants and environmental changes begins at the surface, these changes are detected by components in the plasma membrane, where a molecule receptor generates a lipid signaling cascade via enzymes, such as phospholipases (PLs). Phospholipids are the key structural components of plasma membranes and signaling cascades. They exist in a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 162 publications
(256 reference statements)
0
0
0
Order By: Relevance
“…PLC mediates the plant-pathogen interaction pathways and resistance-related genes in order to enhance basal heat tolerance during the seedling stage. We speculate that inducing pathway-associated molecular patterns (PAMPs) or effector-triggered immunity (ETI) during the seedling stage triggered an immunity enhancement in overall tolerance [38]. During the adult stage, PLC was involved in the ribosome and glycerophospholipid metabolism, and we speculate that it enhanced basal heat tolerance through lipid signaling [12,39].…”
Section: Discussionmentioning
confidence: 96%
“…PLC mediates the plant-pathogen interaction pathways and resistance-related genes in order to enhance basal heat tolerance during the seedling stage. We speculate that inducing pathway-associated molecular patterns (PAMPs) or effector-triggered immunity (ETI) during the seedling stage triggered an immunity enhancement in overall tolerance [38]. During the adult stage, PLC was involved in the ribosome and glycerophospholipid metabolism, and we speculate that it enhanced basal heat tolerance through lipid signaling [12,39].…”
Section: Discussionmentioning
confidence: 96%
“…Phospholipid-based signaling cascades are extremely important in signal transduction as phospholipids activate communication with the immune system preventing invasion by pathogens [62,63]. The main components of this signaling cascade are phospholipase C (PLC) and phospholipase D (PLD), which are also responsible for the turnover of phospholipids along with diacylglycerol kinase (DAK) [64]. Some studies have identified phospholipases involved in plant resistance against fungi and bacteria (mainly in effector recognition) [65,66], as well as in ABA-induced water stress tolerance [67][68][69].…”
Section: Other Proteins' Important In the Process Of Adaptation To Dr...mentioning
confidence: 99%